Surgical techniques for the treatment of acute carpal ligament injuries in the athlete - Gire, J. D.; Yao, J. (Clinics in Sports Medicine, 2020)
The treatment of athletes with carpal ligament injuries provides many challenges. Our initial goals remain to make a timely and accurate diagnosis, provide treatment options, and create an environment for shared decision making. To optimize outcomes and facilitate return to play, early surgical intervention may be warranted. This article reviews common carpal ligament injury patterns in the athlete with a focus on both classic and newer surgical techniques.